The association between transformational leadership and teachers' creativity: professional resilience and job satisfaction as mediators - KAYA, Ayça (Frontiers in Psychology, 2024)
This study investigated the associations between transformational leadership, teachers' job satisfaction, professional resilience, and creativity. The sample included 417 teachers of public and private schools in Istanbul. The data collection tools were “Transformational Leadership Scale”, “Teachers' Professional Resilience Scale”, “Job Satisfaction Scale”, and “Organizational Creativity Scale”. The data analysis was conducted on SPSS and AMOS. A structural equation model (SEM) was employed to test the research hypotheses. The findings suggested that transformational leadership significantly predicted teachers' job satisfaction and professional resilience. However, transformational leadership did not have a statistically significant effect on teachers' creativity. Additionally, teachers' professional resilience was a significant predictor of creativity while job satisfaction was not. Lastly, professional resilience mediated the association between transformational leadership and creativity. Drawing on these findings, it can be concluded that the prevalence of transformational leadership in schools could foster teachers' creativity and professional resilience. Thus, principals should improve their transformational leadership skills and develop strategies to enhance teachers' creative potential. Transformational leadership plays a critical role in fostering teachers' job satisfaction and professional resilience and encourage creativity.